(untitled) (Historia, 2021)
Among historical disciplines, modern social history is one of the fields in which quan- tification is relatively often employed today. Since in Gerinany most professors must represent their fields "in teaching and research" at the same time, the social historian belongs almost automatically to that group of scientists whose profession compels them again and again to think about "Computers and the Humanities." If one glances through the literature or asks around among colleagues who have themselves worked with computers, one quite often runs across a certain resignation. The labor involved in collecting and evaluating the data was often much greater than originally planned. The investment of time which turned out to be necessary for the technical implementation of the project was not, in thematic perspective, com- pensated by the quantity of novel results achieved. The uneasiness reported can be due to various causes: unsuitable source material, technical problems with the computer, but above all, imprecise formulation of the questions, which usually is connected to an insufficient theoretical reflection in the preliminary stages. Often one stands helpless amid a flood of rather irrelevant computer output. A mass of results can be put together in a meaningful whole only with difficulty and with renewed expenditure of time. The stolid efficiency of the computer becomes fateful for its user,who turns awayand gives up